IMPLEMENTATION OF THE POSYANDU PROGRAM FOR THE ELDERLY, IN PLINTAHAN VILLAGE, PANDAAN DISTRICT, PASURUAN REGENCY - Mutiara, Shafa; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to find out how the Posyandu Lansida program is implemented in Plinlahan Village, Pandaan District, Pasuruan Regency, by examining the implementation process. Method: This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation and documentation. George C. Edwards III's (1980) policy implementation theory is used as an analytical knife, with four main variables: communication, resources, disposition, and bureaucratic structure. Results: First, communication was carried out directly by cadres to the elderly due to limited access to technology.  Second, human resources in the form of cadres are quite adequate, supported by a budget from the APBDes for providing additional food (PMT) and honorarium for cadres, although medical equipment is still limited. Third, the disposition or attitude of the cadres shows a high level of concern and dedication towards the smooth running of activities. Fourth, the implementation structure is well organized through division of tasks and coordination between villages, health centers and cadres. Novelty: lies in its focus on the integrated role of cadres, village officials and community health centers in building a community-based health service system for the elderly, as well as how personal communication strategies are an effective solution in reaching targets who are socially and digitally vulnerable.